The Role of Exports, Inflation Management and Human Resources in Preparing for Golden Indonesia 2045 - Leksono, Ari Wahyu; Bratamanggala, Rudi; Saleh, Sugiyanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research explores the critical roles of exports, inflation management, and human resource development in preparing Indonesia for its ambitious